Vectors of Defects in Reinforced Concrete Structures in Onshore Oil and Gas Process Plants - Dabo Baba Hammad; Nasir Shafiq; Muhd Fadhil Nuruddin (Advances in Civil Engineering)
There is a global outcry over the speedy deterioration of structures in oil and gas facilities. While marine environment is considered the leading factor in the deterioration of offshore structures, there is no single factor considered as the main cause of the problem in onshore structures. Therefore, the aim of this paper is to present the result of global survey on the major factors causing the deterioration of concrete structures in onshore oil and gas facilities. To realize the objectives of the paper, an e-questionnaire was administered through two International LinkedIn groups with a membership mainly dominated by experts in onshore oil and gas facilities. 159 respondents completed the questionnaires, and the reliability of the responses was calculated to be 0.950 which is considered excellent. Relative importance index was used in ranking the factors, and it was observed that environmental factors ranked as the dominant factors causing the deterioration of concrete structures in onshore process plants. Another important finding in the study is the role that experience plays on the perception of experts on the causes of defects on concrete structures.